2015
DOI: 10.3402/gha.v8.27271
|View full text |Cite
|
Sign up to set email alerts
|

Causes of death in the Taabo health and demographic surveillance system, Côte d'Ivoire, from 2009 to 2011

Abstract: BackgroundCurrent vital statistics from governmental institutions in Côte d'Ivoire are incomplete. This problem is particularly notable for remote rural areas that have limited access to the health system.ObjectiveTo record all deaths from 2009 to 2011 and to identify the leading causes of death in the Taabo health and demographic surveillance system (HDSS) in south-central Côte d'Ivoire.DesignDeaths recorded in the first 3 years of operation of the Taabo HDSS were investigated by verbal autopsy (VA), using th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

6
4

Authors

Journals

citations
Cited by 26 publications
(43 citation statements)
references
References 24 publications
1
42
0
Order By: Relevance
“…We provide evidence and demonstrate the endemicity of these different bacteria in the studied regions that have the same characteristics agro-ecological and climatic. Furthermore, these diseases could be a cause of death of unknown origin in rural areas in Côte d'Ivoire [ 77 ].…”
Section: Discussionmentioning
confidence: 99%
“…We provide evidence and demonstrate the endemicity of these different bacteria in the studied regions that have the same characteristics agro-ecological and climatic. Furthermore, these diseases could be a cause of death of unknown origin in rural areas in Côte d'Ivoire [ 77 ].…”
Section: Discussionmentioning
confidence: 99%
“…The aim of the present study was to assess the local epidemiology of malaria in the Taabo health and demographic surveillance system (HDSS) of south-central Côte d’Ivoire [ 9 ]. An in-depth analysis of 712 deaths recorded in the Taabo HDSS between 2009 and 2011 revealed that malaria was the most important cause of death (n = 129, 18.0 %) [ 10 ]. Here, results from two cross-sectional surveys conducted in the rainy season of 2010 and 2011 are reported.…”
Section: Introductionmentioning
confidence: 99%
“…This 9-month cluster-randomised, single-blinded, placebo-controlled intervention trial was conducted in the Taabo health and demographic surveillance system (HDSS) in south-central Côte d’Ivoire [ 10 ]. Recently it has been reported that the leading causes of death among children below 5 years of age in the Taabo HDSS are malaria, followed by acute respiratory tract infections and HIV/AIDS [ 11 ]. Malaria transmission is perennial with peaks occurring in the large rainy season (from April to August) and in the small rainy season (September/October).…”
Section: Methodsmentioning
confidence: 99%